2016
DOI: 10.1371/journal.pntd.0004313
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Dengue Virus Transmission in Dar es Salaam, Tanzania during an Epidemic Period of 2014

Abstract: BackgroundIn 2010, 2012, 2013 and 2014 dengue outbreaks have been reported in Dar es Salaam, Tanzania. However, there is no comprehensive data on the risk of transmission of dengue in the country. The objective of this study was to assess the risk of transmission of dengue in Dar es Salaam during the 2014 epidemic.Methodology/Principal FindingsThis cross-sectional study was conducted in Dar es Salaam, Tanzania during the dengue outbreak of 2014. The study involved Ilala, Kinondoni and Temeke districts. Adult m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
156
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(175 citation statements)
references
References 36 publications
12
156
6
1
Order By: Relevance
“…aegypti to measure its efficiency for predicting suitable habitats and areas where targeted environmental management should be conducted. However, data agree well with work of Mboera and colleagues [27] in Dar es Salaam and Lutomiah et al [36] and Ngugi [37] in Mombasa, who identified large items of household waste such as buckets and tyres to be the most important sources of mosquitoes as was seen here in Kinondoni.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…aegypti to measure its efficiency for predicting suitable habitats and areas where targeted environmental management should be conducted. However, data agree well with work of Mboera and colleagues [27] in Dar es Salaam and Lutomiah et al [36] and Ngugi [37] in Mombasa, who identified large items of household waste such as buckets and tyres to be the most important sources of mosquitoes as was seen here in Kinondoni.…”
Section: Discussionsupporting
confidence: 92%
“…africanus, which maintains sylvatic yellow fever, or Ae. albopictus that is a dengue vector currently invading into a number of African countries [40] but has not yet been found in Tanzania [27,41]. Study findings show that higher quality breeding habitats in relatively more wealthy households are likely to be a potential source of Dengue vectors.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Although Ae. aegypti has been reported to be responsible for DENV epidemics in the low-altitude coastal region of Tanzania, 8 the presence of Aedes mosquitoes has not been described in the high altitudes of the Kilimanjaro Region.…”
Section: Introductionmentioning
confidence: 99%
“…Certain genotypes within particular serotypes are associated with epidemics of dengue hemorrhagic fever (DHF) vs. classic dengue [11,13]. Aedes aegypt mosquitoes are the primary vectors of DENV throughout the tropics [14]. DENV infection is categorized as asymptomatic infection, subclinical infection, undifferentiated fever, dengue fever, DHF with or without dengue shock syndrome (DSS) and other severe forms of dengue.…”
Section: Introductionmentioning
confidence: 99%